2020
DOI: 10.1177/0791603520939794
|View full text |Cite
|
Sign up to set email alerts
|

Not collateral damage: Trends in violence and hate crimes experienced by sex workers in the Republic of Ireland

Abstract: The Republic of Ireland’s new Criminal Law (Sexual Offences) Act 2017 (2017 Act) criminalised sex purchase. Drawing on primary data from reports made by sex workers in Ireland to UglyMugs.ie, we analyse trends in violent and other crimes against sex workers in Republic of Ireland (hereafter Ireland). Examining the four-year period 2015–2019, we highlight the various crimes sex workers experience, including incidents of hate crime. Analysis of UglyMugs.ie data found that crimes (including violent offences) agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…We examine various methodologies that have been used in the literature to examine prejudice and to discern the extent of their use in the domains of management, psychology and sociology. Common methodologies include case studies (Paleari et al, 2019), content analysis (Campbell et al, 2020;Lee et al, 2019), experimental design (Apfelbaum et al, 2017), grounded theory (Agarwal, 2016;Rozkwitalska et al, 2016), meta-analysis (Mccord et al, 2018), interviews (Carlson, 2019;Cheung et al, 2016), surveys (Triana et al, 2019;Yu and Duffy, 2020) and the use of MTurk (Jiang, 2018). We examine the methodologies used in the prejudice literature to discern whether different methodologies inform each of the domains examined and whether certain methodologies are more efficacious in studying prejudice in the workplace.…”
Section: Prejudice At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We examine various methodologies that have been used in the literature to examine prejudice and to discern the extent of their use in the domains of management, psychology and sociology. Common methodologies include case studies (Paleari et al, 2019), content analysis (Campbell et al, 2020;Lee et al, 2019), experimental design (Apfelbaum et al, 2017), grounded theory (Agarwal, 2016;Rozkwitalska et al, 2016), meta-analysis (Mccord et al, 2018), interviews (Carlson, 2019;Cheung et al, 2016), surveys (Triana et al, 2019;Yu and Duffy, 2020) and the use of MTurk (Jiang, 2018). We examine the methodologies used in the prejudice literature to discern whether different methodologies inform each of the domains examined and whether certain methodologies are more efficacious in studying prejudice in the workplace.…”
Section: Prejudice At Workmentioning
confidence: 99%
“…Common methodologies include case studies (Paleari et al. , 2019), content analysis (Campbell et al. , 2020; Lee et al.…”
Section: A Levels Of Analysis Perspective On Prejudicementioning
confidence: 99%
“…An analysis of UglyMugs. ie data from 2015 to 2019 (Campbell et al, 2020) found that violence against sex workers increased in the period following the implementation of client criminalisation but that reporting to Gardaí (police) remained low.…”
Section: The Swedish Legislation (Client Criminalisation) Aimsmentioning
confidence: 99%
“…UglyMugs.ie is a mobile phone app and website where sex workers in Ireland can record negative interactions with clients. An analysis of UglyMugs.ie data from 2015 to 2019 (Campbell et al, 2020 ) found that violence against sex workers increased in the period following the implementation of client criminalisation but that reporting to Gardaí (police) remained low.…”
mentioning
confidence: 99%
“…Sex workers face significant barriers to reporting their victimisation (Campbell et al, 2020;McBride et al, 2020;Connelly, Kamerade and Sanders, 2018). As demonstrated within this chapter, the men involved in this study presented as reluctant to report their experiences of harmful behaviour.…”
Section: Barriers To Reportingmentioning
confidence: 99%